Case Report: Severe kidney involvement in a case of very early onset inflammatory bowel disease - Drago, Enrico; Carfora, Roberta; Cafferata, Barbara; Gaggero, Gabriele; Puzone, Laura; La Porta, Edoardo; Signa, Sara; Gandullia, Paolo; Vellone, Valerio Gaetano; Angeletti, Andrea; Arrigo, Serena (Frontiers in Immunology, 2025)
BackgroundPatients affected by very early onset inflammatory bowel disease (VEO-IBD) are frequently refractory to standard treatments. Despite the lack of randomized clinical trials, vedolizumab emerged as an effective and safe alternative treatment in VEO-IBD resistant to TNF antagonists. Here, we present a case of VEO-IBD with ulcerative colitis (UC) phenotype developing renal injury after vedolizumab administration.Case presentationAn 11-year-old female patient with VEO-UC was referred to our clinic for fever, nausea, and fatigue. She was treated with vedolizumab for 1 year due to steroid-dependent disease and failure of multiple therapies, including anti-TNF agents. At admission, she was in steroid-free clinical and endoscopic remission, with leukocytosis, increased inflammatory markers, and a rise in serum creatinine. Urine samples revealed persistent leukocyturia over the past 8–10 months with the absence of lower urinary tract symptoms and negative serial urine culture. MRI showed swollen-looking kidneys with bilateral irregular Diffusion-Weighted Imaging (DWI) signal restriction. Kidney biopsy revealed the presence of acute tubular damage with a mixed interstitial inflammatory infiltrate consistent with drug-induced acute tubulointerstitial nephritis (TIN). After prompt start of systemic glucocorticoid therapy and temporary discontinuation of vedolizumab, normalization of renal function and urinalysis was observed. Vedolizumab was restarted after 2 months, pre-medicated with steroids. The follow-up renal biopsy performed after 6 months showed a regression of the histological pattern, with chronic signs characterized by mild tubular atrophy and interstitial fibrosis.ConclusionVedolizumab-related acute TIN is a potentially severe complication, rarely described in adult patients. We report the first case of VEO-IBD with a probable vedolizumab-related acute TIN treated with corticosteroids, with a good response and maintenance of vedolizumab. Persisting sterile leukocyturia could represent an early sign.